Comparison of fertility following use of one versus two intravaginal progesterone inserts in dairy cows without a CL during a synchronization protocol before timed AI or timed embryo transfer - Pereira, M. H.C. [UNESP]; Sanches, C. P. [UNESP]; Guida, T. G. [UNESP]; Wiltbank, M. C.; Vasconcelos, J. L.M. [UNESP] (Elsevier, 2017)
The objective was to evaluate the effect of increased progesterone (P4) during preovulatory follicle growth during timed AI (TAI) or timed embryo transfer (TET) protocols. Lactating dairy cows with no CL and low circulating P4 (≤1.0 ng/mL) were submitted to a protocol using one or two intravaginal P4 implants (controlled intravaginal releasing device [CIDRs]), and were bred to TAI or TET. The low P4 cows for this experiment were identified on nine farms, four utilized TAI (n = 326 of 1160 cows examined), and five utilized TET (n = 445 of 1396). All cows were synchronized by insertion of P4 implant(s) (CIDR[s]) at start of protocol (Day −11) and simultaneous treatment with 2 mg of E2-benzoate. After 7 days, cows were treated with PGF (Day −4) and 2 days later treated with 1.0-mg E2-cypionate and CIDR(s) were removed (Day −2). Cows received TAI on Day 0 or TET on Day 7. Cows were randomly assigned to receive either one or two CIDRs on Day −11 until Day −2 (1CIDR vs. 2CIDR). Presence of CL was determined by ultrasound on Day −11 and Day 7 after protocol (to determine ovulation to protocol), P4 concentrations were determined on a subset of cows (Day −11, Day −4, Day 7), and ovulatory follicle diameter was evaluated on Day 0. Pregnancy success (P/AI or P/ET) was evaluated on Days 32 and 60. The 2CIDR treatment increased circulating P4 by Day −4 (1.77 ± 0.23 vs. 2.18 ± 0.24 ng/mL) but had no effect on ovulation at the end of protocol (83.6 vs. 82.6%) or ovulatory follicle diameter (15.6 ± 0.3 vs. 15.3 ± 0.3 mm). If only cows that ovulated to the protocol were included, 1CIDR tended to have lower P/AI than 2CIDR by Day 32 (42.8 vs. 52.6%; P = 0.10) and Day 60 (37.7 vs. 48.1%; P = 0.08) but there was no effect on pregnancy loss. There was an interaction (P = 0.05) between ovulatory follicle diameter and CIDR treatment on P/AI (Day 60). In cows ovulating larger follicles (≥14 mm), 2CIDR treatment increased P/AI compared with 1CIDR (53.3 vs. 34.9%; P = 0.02) but not in cows ovulating small follicles (<14 mm). There was no effect of treatment on P/ET on Day 32 (30.0% vs. 32.0%) or Day 60 (24.7% vs. 25.6%). Thus, these results add evidence to the concept that increased circulating P4 during preovulatory follicle development may improve P/AI, most likely due to improved oocyte quality in cows that ovulate larger follicles, since improvement was only in cows ovulating larger follicles and no effect of preovulatory P4 was observed in cows that received ET.
Keywords: CIDR; Progesterone; TAI; TET